Alexander Orbeliani’s Verses - Vakhania, Nino (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
Alexander Orbeliani, romanticist writer, poetic, published, manuscripts Alexander Orbeliani’s verses are not distinguished with high artistic value. Poetically more than consideration he could better write prosaically. Despite of aforesaid his verses have certain significance and have their place in the history of Georgian literature. So,none of the explorers’ of Georgian writing can avoid these verses. In the poetic heritage of romanticist writer is indicated that sorrow caused due to the loss of homeland („Mtovare“). Sorrow and grief is more perfectly and boldly shown in the works written during migration (exile). We find amorous verses that fascinatingly express Georgian nature… Alexander Orbeliani dedicated his verse to Shota Rustaveli, the meter of Georgian poetry. Eulogy is applied on King Erekle in the verse „Epitaph“. There is even expressed so called „World Grief“. According to the verses is found sincere voice of creator, who firstly idolized his land. As Akaki Tsereteli used to state, he „differently loved Georgia“. All verses are not yet published, manuscripts are kept in personal fund. Out of literary heritage of Alexander Orbeliani more noteworthy are prosaic works, though no less interesting are his verses. Among them, to my mind some are outstanding, perfect examples of Georgian romantic poetry.